Toxicity potential in the extraneous compounds of white mulberry wood (morus alba) - Se Golpayegani, Aida; Thévenon, Marie-France; Gril, Joseph; Masson, Eric; Pourtahmasi, Kambiz (Maderas. Ciencia y Tecnología, 2025)
The health problems amongst musical instrument makers working on the White mulberry (Morus alba), lead to investigate the toxicity potential of wood extractives. Five solvents of different polarity and two methods of extractions were used to ensure a thorough, clear and classified compound removal. The compounds were identified using qualitative GC-mass and the toxicity were determined by studying their effect on termite survival (Reticulitermes flavipes). The results indicated the presence of different compound categories like phenols, higher hydrocarbons, fatty acids, sterols and aromatic components in the extractives. These compounds were not removable by just one solvent and the order of removal was polarity related. The extractives were found toxic towards termites. Resorcinol, which corresponded to the highest proportion of peaks in the GC-mass spectra, has been assigned as the possible compound responsible for the allergic reactions by the artisans.